Protein composition and nutritional aspects of pea protein fractions obtained by a modified isoelectric precipitation method using fermentation - Emkani, Mehrsa; Moundanga, Sylvie; Oliete, Bonastre; Saurel, Rémi (Frontiers in Nutrition, 2023)
Pea albumins are promising for their nutritional, biological, and techno-functional properties. However, this fraction is usually discarded in the industry due to its low protein content compared to globulin fraction and the presence of some anti-nutritional compounds. In the present study, we used an alternative method of pea protein extraction based on alkaline solubilization/isoelectric precipitation in which the reduction of pH was achieved by lactic acid fermentation using specific starters instead of mineral acids. Hence, the main objective of this study was to examine the protein profile and the content of anti-nutritional and nutritional active compounds in pea albumin-rich fractions obtained by the isoelectric extraction method without (control) or with fermentation with different lactic acid bacteria (Streptococcus thermophilus, Lactiplantibacillus plantarum, and their co-culture). Different pea cultivars (Cartouche, Ascension, and Assas) were used here for their differences in protein profile. The results revealed a higher total nitrogen content in albumin-rich fraction for fermented samples and, in particular, for co-culture. The majority of total nitrogen was determined as non-protein ( 50%), suggesting the degradation of proteins by LAB to small peptides and amino acids, which were solubilized in the soluble fraction (albumin) as confirmed by size exclusion chromatography (SEC-HPLC) analysis. Moreover, the higher antioxidant activity of fermented albumin samples was attributed to the production of small peptides during extraction. Lactic acid fermentation also resulted in a significant reduction of trypsin inhibitor activity, α-galactoside, and phytic acid content of this fraction compared to control.